Monetary ease: A factor behind financial crises? Some evidence from OECD countries - Rudiger Ahrend (Economics: The Open-Access, Open-Assessment E-Journal, 2010)
This paper addresses the question of whether and how easy monetary policy may lead to excesses in financial and real asset markets and ultimately result in financial dislocation. It presents evidence suggesting that periods when short-term interest rates were persistently and significantly below what Taylor rules would prescribe are correlated with increases in asset prices, especially as regards housing, though no systematic effects are identified on equity markets. Significant asset price increases, however, can also occur when interest rates are in line with Taylor rules, possibly associated with periods of financial deregulation and/or innovation. Finding also some support for a link of countries' pre-crisis monetary stance with the extent to which their financial sectors were hit during the recent crisis, the paper argues that accommodating monetary policy over the period 2002-2005, probably in combination with rapid financial market innovation, would, in retrospect, seem to have been among the factors behind the run-up in asset prices and financial imbalances - the (partial) unwinding of which helped trigger the recent financial market crisis.
Keywords: E44; E5; F3; G15; 330; Interest rates; monetary policy; housing; sub-prime crisis; financial markets; macro-prudential; regulation; Taylor rule; house prices; asset prices; financial imbalances; market turmoil; financial innovation